Variable speed wind turbine generator system with current controlled voltage source inverter - Muyeen, S.M.; Al-Durra, A.; Tamura, J. (Elsevier, 2011)
The present popular trend of wind power generation is to use variable speed wind turbine (VSWT) driving a doubly fed induction generator (DFIG), wound field synchronous generator (WFSG) or permanent magnet synchronous generator (PMSG). Among them, stability analyses of DFIG type of VSWT have already been reported in many literatures. However, transient stability and low voltage ride through (LVRT) characteristics analyses for synchronous generator type of VSWT is not sufficient enough. This paper focuses on detailed LVRT characteristic analysis of variable speed wind turbine driving a PMSG (VSWT-PMSG) with current controlled voltage source inverter (CC-VSI). Modeling and suitable control strategies for overall system are developed to augment the low voltage ride through capability of variable speed wind generator, considering recent wind farm grid code. Both symmetrical and unsymmetrical faults are analyzed as network disturbances in this paper. The permanent fault due to unsuccessful reclosing of circuit breakers is taken into consideration, which is a salient feature of this study. Moreover, the dynamic characteristic is analyzed using real wind speed data measured in Hokkaido Island, Japan. The proposed control scheme is simulated by using the standard power system simulation package PSCAD/EMTDC and results are verified by comparing that of voltage controlled voltage source inverter scheme available in power system literature.